An unusual periosteal tissue in the ribs of two plesiosaurs (Sauropterygia: Plesiosauroidea) from the Upper Cretaceous of Antarctica - Talevi, Marianella (2014)
Fil: Talevi, Marianella. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.